Endocytosis and Exocytosis in Leishmania amazonensis Are Modulated by Bromoenol Lactone - Fernandes, Anne C. S.; Soares, Deivid C.; Neves, Roberta F. C.; Koeller, Carolina M.; Heise, Norton; Adade, Camila M.; Frases, Susana; Meyer-Fernandes, José R.; Saraiva, Elvira M.; Souto-Padrón, Thaïs (Frontiers in Cellular and Infection Microbiology, 2020)
In the protozoan pathogen Leishmania, endocytosis, and exocytosis occur mainly in the small area of the flagellar pocket membrane, which makes this parasite an interesting model of strikingly polarized internalization and secretion. Moreover, little is known about vesicle recognition and fusion mechanisms, which are essential for both endo/exocytosis in this parasite. In other cell types, vesicle fusion events require the activity of phospholipase A2 (PLA2), including Ca2+-independent iPLA2 and soluble, Ca2+-dependent sPLA2. Here, we studied the role of bromoenol lactone (BEL) inhibition of endo/exocytosis in promastigotes of Leishmania amazonensis. PLA2 activities were assayed in intact parasites, in whole conditioned media, and in soluble and extracellular vesicles (EVs) conditioned media fractions. BEL did not affect the viability of promastigotes, but reduced the differentiation into metacyclic forms. Intact parasites and EVs had BEL-sensitive iPLA2 activity. BEL treatment reduced total EVs secretion, as evidenced by reduced total protein concentration, as well as its size distribution and vesicles in the flagellar pocket of treated parasites as observed by TEM. Membrane proteins, such as acid phosphatases and GP63, became concentrated in the cytoplasm, mainly in multivesicular tubules of the endocytic pathway. BEL also prevented the endocytosis of BSA, transferrin and ConA, with the accumulation of these markers in the flagellar pocket. These results suggested that the activity inhibited by BEL, which is one of the irreversible inhibitors of iPLA2, is required for both endocytosis and exocytosis in promastigotes of L. amazonensis.